2005
DOI: 10.1159/000086908
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility in reciprocal translocation carriers: the sex body affair

Abstract: Previous reports have linked chromosomal reorganization and spermatogenic failure. In this context, it has long been known that reciprocal translocation carriers are more likely to have anomalies in the meiotic process, including fertility failures. It has also been proposed that this fertility failure may be a consequence of an association between the translocated chromosomes and the sex body. In this work, we review different hypotheses explaining meiotic failure in these carriers, and propose a model that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
2
34
0
1
Order By: Relevance
“…In human male infertile patients, carriers of heterozygous chromosomal rearrangements, a similar XY association with multivalents (Rosenmann et al, 1985;Johannisson et al, 1987;reviewed in Gabriel-Robez and Rumpler, 1994) or univalents (Jaafar et al, 1994) has been repeatedly reported. The hypothetical, pathogenetic role of this association of autosomal chromatin with the non-transcribing (silenced; Monesi, 1965) XY body has been also reported by several authors (reviewed in Solari, 1999 andin Oliver-Bonet et al, 2005a).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In human male infertile patients, carriers of heterozygous chromosomal rearrangements, a similar XY association with multivalents (Rosenmann et al, 1985;Johannisson et al, 1987;reviewed in Gabriel-Robez and Rumpler, 1994) or univalents (Jaafar et al, 1994) has been repeatedly reported. The hypothetical, pathogenetic role of this association of autosomal chromatin with the non-transcribing (silenced; Monesi, 1965) XY body has been also reported by several authors (reviewed in Solari, 1999 andin Oliver-Bonet et al, 2005a).…”
Section: Introductionsupporting
confidence: 57%
“…Thus, as previously suggested (Solari, 1999), heterologous synapsis may be a way to 'escape' from the damaging results of asynapsis and association with the XY body, both of which have been suspected to activate a pachytene checkpoint that may lead to apoptosis (Odorisio et al, 1998) or a damaging transcriptional inactivation (Solari, 1999;Oliver-Bonet et al, 2005a).…”
Section: Discussionmentioning
confidence: 79%
“…[12][13][14] Anomalies in any of the acrocentric chromosomes may increase the risk of sterility too. In our patient, infertility could be due to an abnormal pattern of meiotic recombination in abnormal oocytes that showed chromosomepairing errors.…”
Section: Discussionmentioning
confidence: 99%
“…55,59 Furthermore, chromosome imbalances in offspring, in which either of the parents carries chromosomal structural abnormalities such as translocations or inversions, often originate from maternal gametes, whereas such chromosomal abnormalities occasionally cause azoospermia due to meiotic arrest when they are present in male mice. 74 As these structural abnormalities obviously impair complete synapsis during meiotic prophase, this phenotypic disparity may also be accounted by the checkpoint differences between female and male mice.…”
Section: Mechanism Of Chromosomal Abnormalities H Kurahashi Et Almentioning
confidence: 99%